Associations between religiosity, mental health, and subjective well-being among Arabic samples from Egypt and Kuwait - Abdel-Khalek, Ahmed M. (Mental health, religion & culture, 2012)
Two samples of Egyptian (n = 577) and Kuwaiti (n = 674) college students recruited to (a) explore the sex-and country differences in religiosity, mental health, and subjective well-being, (b) estimate the associations between and factors from the last-mentioned variables, and (c) explore the predictors of religiosity. The participants completed the Arabic Scale of Mental Health, the Rosenberg Self-esteem Scale and five self-rating scales to assess religiosity, physical health, mental health, happiness, and satisfaction with life. Egyptian and Kuwaiti men obtained significantly higher mean scores than did their female counterparts. Kuwaiti men and women had significantly higher mean scores on all the scales than their Egyptian counterparts. All the correlations between the scales were significant and positive. A highly loaded factor was identified and labelled Mental health, well-being and religiosity. Stepwise regression indicated that the main predictors of religiosity were self-esteem, happiness, satisfaction and mental health in different combinations.